“Papan emosi” to improve emotional expression activity of the resident drug rehabilitation in Banda Aceh, Indonesia - Haiyun Nisa; Herman Rabu (Proceedings of AICS - Social Sciences, 2013)
This study aims to understand how the role of the "papan emosi " in increasing emotional expression activity of resident drug rehabilitation in Banda Aceh.  The participant of this study are 15 residents that was a drug addiction, male, age 12 – 44 years old and came from many district of Aceh. Drugs affect many factors, namely physical, emotional, spiritual and social. Emotional is one factor that very influenced to people. Most of them feel  a empty emotion that called frozen feeling. They feel is very difficult to express their feeling, although they have daily activity to write emotional journal. “Papan emosi” is one of activity that we can use to express emotion because emotional expression is one of points that very important for residents in rehabilitation. Most of them felt that very difficult to express emotions. The approach used in this study is phenomenological approach that viewed subjects in their natural context. Method of data collection is done by looking at how the activities undertaken emotional expression through "papan emosi" that shows emotions what they are feeling. The results showed that they are very happy with “papan emosi”, that can helped them to express their feeling without saying to others, but they can use emotion’s symbols. “Papan emosi” are also useful for counselors so knowing the emotional state resident who is being accompanied.Keywords:“papan emosi”, resident drug rehabilition, Banda Aceh